Strategi Pemasaran Umkm Warung Nasi Sunda Ibu Titing Melalui Pendekatan Analisis Swot dan Marketing Mix - Firmansyah, Irman; Akbar, Ridho Riadi; Jaya, Rama Chandra (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study explores the marketing strategy of Warung Nasi Sunda Ibu Titing, a micro, small, and medium enterprise (MSME) that has been operating since 2004 and faces challenges such as intense competition, limited facilities, and low adoption of digital technology. The problem statement revolves around efforts to enhance competitiveness through effective strategies. The research methodology employs a qualitative descriptive approach using SWOT analysis to identify strengths, weaknesses, opportunities, and threats, complemented by the Marketing Mix (4P) framework to develop a comprehensive marketing strategy. The findings reveal that Warung Nasi Sunda Ibu Titing’s main strengths include a diverse menu, high-quality products, and a strategic location. However, weaknesses such as minimal digital promotion and limited parking facilities pose significant challenges. Opportunities arise from modern culinary trends and government policies supporting MSMEs, which can be leveraged to expand the market. Threats from more innovative competitors and the instability of raw material prices require adaptive strategies. The study concludes by recommending strategies such as expanding digital services through online platforms, enhancing social media promotion, and introducing menu innovations to attract new customer segments. Implementing these strategies is expected to help Warung Nasi Sunda Ibu Titing maintain its presence and improve competitiveness in the culinary market.